Progress in Lens and Cataract Research 2002
DOI: 10.1159/000060811
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Ultraviolet Radiation Exposure to the Lens Expressed by Maximum Tolerable Dose

Abstract: The maximum tolerable dose (MTD2.3:16) for avoidance of cataract on exposure to ultraviolet radiation (UVR)-300 nm in the rat was here estimated at 3.65 kJ/m2. Sprague-Dawley rats were unilaterally exposed to UVR in the 300 nm wavelength region. One week after the exposure, the intensity of forward light scattering was measured. Toxicity for continuous response events can be estimated with MTD. Current safety standards for avoidance of cataract after exposure to UVR are based on a binary response event. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 13 publications
(14 reference statements)
3
46
0
Order By: Relevance
“…Maximum sensitivity of the rat lens to UVR-B is around 300 nm. The dose 1 kJ/m 2 was chosen to be below the threshold dose 15 . The exposure time of 15 min was selected to induce maximum damage to the lens 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Maximum sensitivity of the rat lens to UVR-B is around 300 nm. The dose 1 kJ/m 2 was chosen to be below the threshold dose 15 . The exposure time of 15 min was selected to induce maximum damage to the lens 21 .…”
Section: Discussionmentioning
confidence: 99%
“…12 In order to estimate threshold dose despite the fact that there is no absolute threshold for in vivo UVR-induced cataract, it was suggested to use the maximum tolerable dose, (MTD 2.3:16 ), as a meaningful estimate of toxic dose. 13 It was demonstrated that reciprocity largely holds for in vivo UVR-300 nm exposures in the exposure time interval 7.5-120 min, but there is a slightly higher sensitivity with exposure times of around 15 min (Figure 6). 14 The slightly higher sensitivity for exposures around 15 min was attributed to the depletion of preexisting anti-oxidation defense.…”
Section: Experimental Evidencementioning
confidence: 95%
“…UVA makes up most of the UVR reaching the earth. UVB makes up merely 5% of the UVR reaching the earth, and UVC does not reach the earth at all [3, 4, 5, 6, 7, 8, 9, 10, 11]. The UVR with a wavelength of less than 295 nm are all absorbed by the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…The UVR with a wavelength of less than 295 nm are all absorbed by the cornea. As far as the wavelengths between 295 and 400 nm (UVB and UVA) are concerned, these reach and are then absorbed by the lens [3, 4, 5, 6, 7, 8, 9, 10, 11]. The most important pathological effect induced by UVR on the lens is cataract formation, which occurs either directly or indirectly on the grounds of the lens being exposed to UVR for long years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation